2018
DOI: 10.20961/eed.v6i3.35904
|View full text |Cite
|
Sign up to set email alerts
|

Using Dialogue Journal to Improve Students’ Writing Proficiencies

Abstract: <p>Dialogue journal is perceived as an effective technique for teaching writing. This article aims at reporting a study on the use of Dialogue journal to improve students’ writing proficiencies. The objectives of the research were to know how dialogue journal can be implemented effectively to improve students’ writing proficiencies and to know to what extent dialogue journal can improve their writing proficiencies. A classroom action research was conducted in a group of students in one of state junior hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Although this study did not distinguish students' proficiency levels as conducted by Madeng and Palanukulwong (2019), the increasing number of words on students' writing production from regular writing activities to ODJW revealed that the students were more willing to write. Nevertheless, since few students were found to have either a stagnant or less number of words, it can be assumed that there were some factors underlying the phenomenon, which might be proficiency level, or more specifically, limited vocabulary (Hapsari et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although this study did not distinguish students' proficiency levels as conducted by Madeng and Palanukulwong (2019), the increasing number of words on students' writing production from regular writing activities to ODJW revealed that the students were more willing to write. Nevertheless, since few students were found to have either a stagnant or less number of words, it can be assumed that there were some factors underlying the phenomenon, which might be proficiency level, or more specifically, limited vocabulary (Hapsari et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional implementation of DJW seems to affect students' productivity in such a way that they boost the number of words in ODJW. The absence of correction to their writing might be one of the factors causing the increase of productivity and students' pleasant feelings, as revealed by their responses toward the writing prompt in a nonthreatening atmosphere (Hapsari et al, 2018). However, students mentioned that they still pay attention to the grammar and other rules of writing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations